A critical review on plant biomonitors for determination of polycyclic aromatic hydrocarbons (PAHs) in air through solvent extraction techniques. (July 2020) - Mukhopadhyay, Shritama; Dutta, Ratna; Das, Papita
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are hydrocarbons having two or more fused aromatic rings, released from natural (like forest fires and volcanic eruption) as well as man-made sources (like burning of fossil fuel & wood, automobile emission). They are persistent priority pollutants and continue to last for a long time in the environment causing severe damage to human health owing to their genotoxicity, mutagenicity and carcinogenicity. The study of PAHs in environment has therefore aroused a global concern. PAHs adsorption to plant cell wall is facilitated by transpiration and plant root lipids which help PAHs transfer from roots to leaves and stalks, causing more accumulation of contaminants with the increase in lipid content. Hence, these bioaccumulators can be utilized as biomonitors for indirect assessment of ambient air pollution. Efficacy of specific plants, lichens and mosses as useful biomonitors of airborne PAHs pollution has been discussed in this review along with prevalent classical and modified extraction techniques coupled with proper analytical procedures in order to gain an insight into the assessment of atmospheric PAHs concentrations. Different modern and modified solvent extraction techniques along with conventional Soxhlet method are identified for extraction of PAHs from accumulative bioindicators and analytical methods are also developed for accurate determination of PAHs. Process parameters like choice of solvent, temperature, time of extraction, pressure and matrix characteristics are usually checked. An approach of biomonitoring of PAHs using plants, lichens and mosses has been discussed here as they usually trap the atmospheric PAHs and mineralize them. Graphical abstract: Image 1 Highlights: Monitoring of ambient concentration of 16 USEPA PAHs using biomonitors for evaluation of air quality Different plant biomonitors based on APTI and IAP values for quantification of ambient PAHs Morphological characteristics of plants greatly influence accumulation of PAHs in their tissues over time Conventional and modified solvent extraction techniques for determination of PAHs from different biomonitors. Different plant bioindicators used till date for assessment of ambient PAHs